2016
DOI: 10.1128/aem.01094-16
|View full text |Cite
|
Sign up to set email alerts
|

Novel Group of Leaderless Multipeptide Bacteriocins from Gram-Positive Bacteria

Abstract: From raw milk we found 10 Lactococcus garvieae isolates that produce a new broad-spectrum bacteriocin. Though the isolates were obtained from different farms, they turned out to possess identical inhibitory spectra, fermentation profiles of sugars, and repetitive sequence-based PCR (rep-PCR) DNA patterns, indicating that they produce the same bacteriocin. One of the isolates (L. garvieae KS1546) was chosen for further assessment. Purification and peptide sequencing combined with genome sequencing revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 39 publications
0
90
0
Order By: Relevance
“…We have previously shown that synthetic GarKS is functionally comparable to the biologically produced counterpart (31). Synthetic GarKS (with > 90% purity) has a specific activity of 130-140 BU/µg.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…We have previously shown that synthetic GarKS is functionally comparable to the biologically produced counterpart (31). Synthetic GarKS (with > 90% purity) has a specific activity of 130-140 BU/µg.…”
Section: Resultsmentioning
confidence: 93%
“…It is well known that bacteria are ecologically adapted to the environments where they normally thrive. Since the producer KS1546 was isolated from raw milk (31), we examine the possibility to use skim milk (SM) as growth medium. Bacteriocin production was increased 2-fold in SM (160 BU/ml) compared to GM17 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations